Preparation method of magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers
By using magnetothermal nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflower in the treatment of bacterial pneumonia, combined with magnetothermal therapy, piezoelectric catalytic therapy and enzyme activities, a new antibacterial nanomaterial was formed, which solved the treatment problems brought about by antibiotic resistance and achieved efficient multiple antibacterial effects.
Patent Information
- Application Number
- CN202411896661.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The prior art is difficult to effectively solve the treatment problems of patients with bacterial pneumonia, especially in the context of antibiotic resistance, and a single antibacterial treatment method is difficult to achieve ideal results.
Magnetic thermal nanoparticles preparation method based on piezoelectric catalytic molybdenum disulfide nanoflower is adopted, combining magnetothermal therapy (MHT), piezoelectric catalytic therapy (PCT) and enzyme activities to form a new antibacterial nanomaterial, enhancing the synergistic effect of each single treatment method and achieving multiple antibacterial effects.
By integrating magnetothermal, piezoelectric catalysis and enzyme activities, the antibacterial treatment efficiency is significantly improved, and it has efficient antibacterial and bactericidal ability for multidrug-resistant bacteria, reducing adverse reactions and improving the therapeutic effect of bacterial pneumonia.
Smart Images

Figure CN119700971A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of preparation of antibacterial and anti-inflammatory nanoparticles, and specifically relates to a method for preparing magnetocaloric nanoparticles based on piezoelectric catalysis of molybdenum disulfide nanoflowers. Background Art
[0002] Bacteria can be found everywhere in our lives. Most bacteria, such as those in the intestines, are not only harmless to the human body, but some are also beneficial to the human body. However, once some bacteria enter the host and reproduce, they will cause infection. Bacterial pneumonia accounts for 80% of all types of pathogen pneumonia in adults. It is one of the common clinical diseases and the most common pneumonia. Staphylococcus aureus, Pseudomonas aeruginosa, Streptococcus pneumoniae, Klebsiella pneumoniae, Haemophilus influenzae, etc. can cause bacterial pneumonia, leading to severe lung damage, impaired respiratory function, and even death. Since the advent of the antibiotic era, the prognosis of bacterial pneumonia has improved significantly. While killing or inhibiting the growth of bacteria, these antibiotics have brought selection pressure to the survival of bacteria. Under the influence of multiple factors such as antibiotic selection pressure and antibiotic abuse, bacteria gradually become resistant, which brings difficulties and challenges to the treatment of patients with bacterial pneumonia. In order to change this situation, researchers have come up with many new methods to replace traditional antibiotic treatments, such as phage antibacterial, the combination of antibody antibiotics and nanomaterials therapy, which have been experimentally proven to be effective. Excitingly, nanomaterial therapy has made remarkable progress in the field of antibacterial treatment and has shown great development potential. Nanomaterials have a series of unique advantages due to their diverse composition. Nanomaterials with specific physical and chemical properties can respond to stimuli such as light, ultrasound and alternating magnetic fields, thereby showing high antibacterial properties in specific environments, such as new treatment modes such as photodynamic therapy (PDT), sonodynamic therapy (SDT), piezoelectric catalytic therapy (PCT) and magnetic hyperthermia therapy (MHT). Compared with light, ultrasound can be focused to a three-dimensional high scatter point in deep tissues, while light diffuses very significantly when passing through tissues, and its penetration depth is also very limited, resulting in SDT being much better than PDT in the treatment of deep lesions.
[0003] Piezocatalytic therapy (PCT) has emerged as a novel therapeutic modality for ultrasound-mediated generation of reactive oxygen species (ROS), such as hydroxyl radicals (·OH), superoxide anions (·O2 - ) and singlet oxygen ( 1O2) Similar to the principle of SDT, the sonosensitizer of piezoelectric materials can be excited by low-frequency ultrasound to produce activated electrons and holes, which can participate in the redox reaction of O2 or H2O to produce ROS. With their unique piezoelectric effect, piezoelectric materials such as barium titanate (BaTiO3), MoS2 nanosheets and black phosphorus can immediately generate a built-in electric field when subjected to external mechanical stress. Under ultrasonic excitation, piezoelectric materials are polarized, and electrons gather on one side, but quickly neutralize the surrounding charges, which greatly limits their catalytic performance. To this end, we construct a piezoelectric nanoheterojunction. When the heterojunction is formed, the polarized electrons excited by ultrasound are effectively migrated at the interface; therefore, the yield of electrons can be increased to produce more ROS. However, it is difficult for a single PCT to achieve the ideal antibacterial effect. It can be combined with other highly penetrating treatments to effectively and synergistically fight against lung infection lesions.
[0004] MHT is an emerging physical hyperthermia technology that uses magnetic nanomaterials to generate heat through hysteresis or relaxation loss under an external alternating magnetic field, thereby rapidly raising the temperature of the lesion to 45°C-50°C to kill bacteria. Compared with other hyperthermia treatments, MHT has shown great advantages in overcoming some common limitations, such as poor conformity of microwave and radiofrequency ablation, the inability of ultrasound to penetrate gas cavities, and limited penetration of light into the human body. Therefore, magnetic hyperthermia is considered to be one of the most promising physical therapies for treating deep lesions, providing a new option for safer and more effective antibacterial treatment. However, MHT has obvious limitations, namely the need for high doses of MNPs. To this end, researchers have developed a number of combined treatments to overcome the defect that a single treatment mode is difficult to completely cure tissue infection in order to achieve the best treatment effect. The combined treatment of PCT and MHT enhances their synergistic effect to improve the efficiency of antibacterial treatment while minimizing adverse reactions.
[0005] At present, emerging exogenous stimulation therapies (such as magnetic field, ultrasound, heat and light) have been used to treat bacterial infection sites. Under the action of exogenous stimulation, stimulus-responsive biomaterials can achieve on-demand antibacterial effects by changing their own physicochemical properties, so they show great application prospects in the future. However, the bioavailability of these methods is relatively low. In addition, when bacteria invade, the microenvironment of bacterial infection is often accompanied by changes in multiple factors, such as neutrophil increase, high proteolytic enzyme content, high local temperature, weak acidity, and low oxygen concentration. It is also accompanied by overexpression of hydrogen peroxide (H2O2) and ROS in the inflammatory area. Compared with exogenous stimulation, endogenous stimulation in the disease microenvironment (for example, pH, enzymes, redox or glucose) is region-specific, which can respond to changes in the wound microenvironment in a timely manner and minimize infection. Nanomaterials with enzyme-like properties, namely nanozymes, have microenvironment-responsive catalytic activity. In particular, nanozymes including peroxidase (POD), oxidase (OXD), catalase (CAT), etc. can simultaneously produce ROS or eliminate ROS to maintain the balance of intracellular ROS, effectively eradicating bacteria and even biofilms in the infected area, while producing O2 to relieve local inflammation in the bacterial infection microenvironment. However, both exogenous and endogenous stimulus-responsive platforms can affect the activity of bacteria, but strategies based on a single stimulus often show insufficient antibacterial performance, especially for the elimination of biofilms. Therefore, the development of an antibacterial platform that is both endogenous and exogenous stimulus-responsive is of great significance for the efficient sterilization of infected lesions. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers, which can integrate MHT, PCT and enzyme activity into a new type of antibacterial nanomaterial, enhance the synergistic effect of each single treatment method, achieve multiple antibacterial effects, and improve the treatment efficiency of bacterial pneumonia.
[0007] The technical solution adopted by the present invention is as follows:
[0008] A method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers, the preparation method comprising the following steps:
[0009] S1: Preparation of MoS2;
[0010] In the S1, the preparation steps of MoS2 are as follows:
[0011] Weigh 1.235 g of ammonium molybdate and 1.052 g of thioacetamide and dissolve them in 20 mL of deionized water. Stir evenly to obtain a colorless transparent solution. Transfer it to a 50 mL high-pressure reactor and react at 220 ° C for 8 h. Wash it repeatedly with distilled water and anhydrous ethanol for many times. The product is vacuum dried at 60 ° C for 48 h to obtain MoS2.
[0012] S2: preparing MnFe2O4;
[0013] In the S2, the preparation steps of MnFe2O4 are as follows:
[0014] S21: MnCl2·4H2O, FeCl3·6H2O and NaOH are the main co-precipitates, and M Mn :M Fe =1:4 ratio, MnCl2·4H2O and FeCl3·6H2O are accurately dissolved in a certain amount of distilled water to obtain a salt solution;
[0015] S22: Under magnetic stirring, NaOH solution was added to the salt solution, the pH value was maintained at 9, and the mixture was vigorously stirred at room temperature for 30 min to obtain a brown-black colloidal mixture;
[0016] S23: Then, the brown-black colloidal mixture is placed into a polytetrafluoroethylene liner, and the liner is placed into a high-pressure reactor, and a constant temperature reaction is carried out at 200° C. for 16 hours;
[0017] S24: Wash with distilled water and anhydrous ethanol for multiple times, dry the product in vacuum at 60°C for 48h, and grind to obtain MnFe2O4.
[0018] S3: Preparation of MoS2@MnFe2O4 nanocomposite materials;
[0019] In S3, the preparation steps of the MoS2@MnFe2O4 nanocomposite material are as follows:
[0020] S31: First, weigh 0.462 g of MnFe2O4 and put it into 10 ml of deionized water, and ultrasonically vibrate for 30 minutes to obtain solution A;
[0021] S32: Dissolve 1.235 g of ammonium molybdate and 1.052 g of thioacetamide in 10 mL of deionized water and stir evenly to obtain solution B;
[0022] S33: Solution A and solution B were mixed and placed in a shaker for 30 min, and then transferred to a high-pressure reactor for reaction at 220° C. for 8 h;
[0023] S34: Wash with distilled water and anhydrous ethanol for several times, and dry the product in vacuum at 60°C for 48h.
[0024] S4: Preparation of MoS2@MnFe2O4@PVP;
[0025] In the S4, the preparation steps of MoS2@MnFe2O4@PVP are as follows:
[0026] S41: 10 mg of MoS2@MnFe2O4 nanoparticles were dissolved in 10 mL of deionized water and ultrasonically shaken for 30 min to obtain a black suspension A;
[0027] S42: Dissolve 40 mg of polyvinyl pyrrolidone in 10 mL of deionized water to obtain a clear and transparent solution B;
[0028] S43: Under the action of ultrasound, solution A was slowly added dropwise to solution B, and ultrasound was continued for 10 min. Then, the solution was placed in a 37°C constant temperature shaker and shaken at 180 rpm for 12 h to obtain solution C.
[0029] S44: Solution C was repeatedly washed with anhydrous ethanol and deionized water for three times, dried under vacuum at 60°C overnight and ground to obtain MoS2@MnFe2O4@PVP nanoparticles.
[0030] S5: Determine the antibacterial properties of MoS2@MnFe2O4@PVP nanocomposites;
[0031] In said S5, the antibacterial properties of the nanocomposite materials were studied using MRSA and MDR-Kp as model bacteria by using a plate coating method, and the colonies did not significantly decrease after co-incubation with physiological saline and applying stimulation conditions thereto;
[0032] Under the synergistic effect of magnetic heat and ultrasound, the antibacterial efficiency of the nanocomposite material against MRSA and MDR-Kp reached 99.5% and 99.8% respectively, and the nanocomposite material had in vitro antibacterial ability.
[0033] S6: Evaluation of the anti-biofilm ability of MoS2@MnFe2O4@PVP nanocomposites in vitro;
[0034] In S6, MRSA and MDR-Kp were used to evaluate the in vitro anti-biofilm activity, and the evaluation steps were as follows:
[0035] S61: Place a 9 mm cell slide into a 24-well plate and add 1 mL of 1×10 7 CFU / mL of MRSA or MDR-Kp suspension was inoculated into the wells containing cell slides;
[0036] S62: Incubate continuously in a biochemical incubator at 37°C for 96 hours, during which the culture medium is replaced every 24 hours to form a biofilm on the surface; after the biofilm is formed, wash repeatedly with sterile saline to remove unbound bacteria;
[0037] S63: After treatment under different conditions, the bacteria were labeled with SYTO9 and PI dyes in dark conditions, incubated for 30 min, rinsed three times with sterile saline, and the fluorescence imaging effect of live and dead bacteria was performed under a laser confocal microscope;
[0038] S64: In MDR-Kp or MRSA, the mortality of the MMP-treated groups was higher than that of the control group, demonstrating that the nanocomposite played a significant role in disrupting the biofilm.
[0039] S7: Verify the therapeutic effect of MoS2@MnFe2O4@PVP nanocomposite on bacterial pneumonia in vivo.
[0040] In S7, the steps of verifying the treatment effect are as follows:
[0041] S71: A BALB / C mouse lung infection model induced by MDR-Kp was established, and 7 different groups were treated separately, including PBS, PBS+AMF+US, MMP, MMP+US, MMP+AMF, MMP+AMF+US, and Health;
[0042] S72: Lung tissue homogenate was collected and smeared on the 3rd day after treatment, and the residual bacteria in the lung tissue were evaluated by plate smear counting method;
[0043] S73: There were obvious bacteria in the lung tissues of other treatment groups, and the number of bacteria in the lungs of mice treated with MMP+AMF+US was significantly reduced;
[0044] S74: In the PBS group, PBS+AMF+US group, and MMP group, CD86 was highly expressed in the lungs, which enhanced the inflammatory response and induced lung injury; in the MMP+AMF+US group, CD86 protein was significantly downregulated, while CD206 expression was at its peak, and MMP+AMF+US treatment had antibacterial ability in mice.
[0045] The technical effects achieved by the present invention are:
[0046] The present invention discloses a method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers, which uses a new type of antibacterial nanomaterial that integrates MHT, PCT and enzyme activity to enhance the synergistic effect of each single treatment method, achieve multiple antibacterial effects, and improve the treatment efficiency of bacterial pneumonia; and MMP takes MnFe2O4 as the core, and when an alternating magnetic field is applied, the temperature is increased to kill bacteria and promote the efficiency of PCT in producing ROS.
[0047] The present invention provides a method for preparing magnetocaloric nanoparticles based on piezoelectric catalysis of molybdenum disulfide nanoflowers. MMP can exert different enzymatic activity effects under the bacterial infection microenvironment at different stages, and improve the reaction efficiency of enzyme activity through the joint action of magnetocaloric and piezoelectric catalysis, accelerate the production of ROS and O2, kill bacteria and promote the polarization of macrophages, activate the body's immune response and regulate lung inflammation. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 is a schematic diagram of an embodiment of the present invention;
[0049] Figure 2a is a SEM image of the MoS2 nanomaterial according to an embodiment of the present invention;
[0050] Figure 2b is the XRD spectrum of MoS2 of the embodiment of the present invention;
[0051] Figure 3a is a SEM image of the MnFe2O4 nanomaterial of the embodiment of the present invention;
[0052] Figure 3b is the XRD spectrum of MnFe2O4 in the embodiment of the present invention;
[0053] Figure 4a is the SEM image of MoS2@MnFe2O4 synthesized in different molar ratios in the embodiments of the present invention;
[0054] Figure 4b is the DLS particle size distribution of MoS2@MnFe2O4 synthesized at different molar ratios in the embodiments of the present invention;
[0055] Figure 4c is the XRD spectrum of MoS2@MnFe2O4 synthesized in different molar ratios in the embodiments of the present invention;
[0056] Figure 5a It is the magnetocaloric temperature rise curve of MoS2@MnFe2O4 synthesized in different molar ratios in the embodiment of the present invention in AMF;
[0057] Figure 5b It is a comparison diagram of the degradation rate of DPBF of MoS2@MnFe2O4 synthesized in different molar ratios in the embodiment of the present invention under ultrasonic irradiation;
[0058] Figure 5c This is a comparison chart of the degradation rates of DPBF under ultrasonic irradiation of MoS2@MnFe2O4 synthesized at different molar ratios under a heating environment in an embodiment of the present invention;
[0059] Figure 6a is a SEM image of the MMP of the embodiment of the present invention;
[0060] Figure 6b is a TEM image of the MMP of the embodiment of the present invention;
[0061] Figure 6c is an EDS element mapping image of the MMP of an embodiment of the present invention;
[0062] Figure 6d is the XRD pattern of the MMP of the embodiment of the present invention;
[0063] Figure 6e is the FTIR spectrum of the MMP of the embodiment of the present invention;
[0064] Figure 7a is the UV-visible-diffuse reflectance spectrum of different samples in the embodiments of the present invention;
[0065] Figure 7b is the photoluminescence spectra of different samples of the embodiments of the present invention;
[0066] Figure 7c 1 is an electrochemical impedance diagram of different samples of the embodiment of the present invention;
[0067] Figure 7d is the transient current response of the ultrasonic on / off state of the embodiment of the present invention;
[0068] Figure 7e The ESR test of MMP under different conditions in the embodiment of the present invention 1 O2 production;
[0069] Figure 7f Schematic diagram of the energy band structure of the MMP according to an embodiment of the present invention;
[0070] Figure 7g It is the hysteresis loop test of the MMP of the embodiment of the present invention;
[0071] Figure 7h is the magnetothermal temperature rise curve of MMP at different concentrations in the embodiment of the present invention;
[0072] Figure 7i is the magnetocaloric cycle curve of the MMP of the embodiment of the present invention;
[0073] Figure 8a is the POD enzyme activity of the MMP of the present invention;
[0074] Figure 8b is the change in absorbance at 652 nm of the POD enzyme activity of different samples in the examples of the present invention over time;
[0075] Figure 8c is an ESR spectrum for detecting OH in an embodiment of the present invention;
[0076] Figure 8d This is the situation of producing O2 by MoS2, MnFe2O4 and MMP catalyzing H2O2 under different pH conditions in the embodiments of the present invention;
[0077] Figure 8e is the absorbance of MMP at 410 nm under different stimulation conditions in the examples of the present invention;
[0078] Figure 9a It is a picture of the bacterial plate-spread colonies after different treatments in the embodiments of the present invention;
[0079] Figure 9b The embodiment of the present invention is based on Figure 9a The survival statistics of MRSA and MDR-Kp (n=3);
[0080] Fig.10a 3DCLSM images of biofilms stained by live / dead double staining scheme under different treatment conditions in the examples of the present invention;
[0081] Fig.11a This is a photo of bacterial colonies on a plate of lung tissue homogenate of infected mice after different treatments in an embodiment of the present invention;
[0082] Fig.11b It is the quantitative statistics of colonies on the lung homogenate plate of infected mice after different treatments in the examples of the present invention (n=3);
[0083] Fig.11c This is the immunohistochemical analysis of CD206 and CD86 in lung tissues of infected mice after different treatments according to the examples of the present invention. DETAILED DESCRIPTION
[0084] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is specifically described below in conjunction with embodiments. It should be understood that the following text is only used to describe one or several specific embodiments of the present invention, and does not strictly limit the scope of protection of the specific claims of the present invention.
[0085] Diseases caused by bacterial infections, such as skin wound infections, respiratory and lung infections, and soft tissue infections, are often treated with antibiotics. However, with the abuse of antibiotics, a large number of drug-resistant bacteria have emerged, and antibiotic-resistant (AMR) bacterial infections have become a global health crisis. At present, there are many treatment strategies for bacterial infections, such as PTT, PDT, and CDT. In general, single-mode antibacterial strategies are limited and difficult to achieve ideal antibacterial effects. In addition, PTT and PDT cannot penetrate deep tissues and are only effective and applicable in the treatment of superficial infections. The present invention has developed a new nanoformulation MoS2@MnFe2O4@PVP (MMP), which is used for the treatment of deep-seated bacterial pneumonia. In addition to the effects of MHT and PCT, the nanoformulation can efficiently sterilize deep-seated infection lesions, and can also exert multiple enzyme activities in different bacterial infection micro-acid environments, improve antibacterial efficiency, and enhance the body's immune regulation function for inflammatory sites. In addition, magnetothermal and piezoelectric catalysis can cascade enhance nanoenzyme activity. MMP nanoparticles, as a safe and effective integrated antibacterial and anti-inflammatory nanoformulation, provide a new approach to replace traditional antibiotics in the treatment of bacterial diseases.
[0086] like Figure 1 As shown, a method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers, the preparation method comprises the following steps:
[0087] S1: Preparation of MoS2;
[0088] In the S1, the preparation steps of MoS2 are as follows:
[0089] Weigh 1.235 g of ammonium molybdate and 1.052 g of thioacetamide and dissolve them in 20 mL of deionized water. Stir evenly to obtain a colorless transparent solution. Transfer it to a 50 mL high-pressure reactor and react at 220 ° C for 8 h. Wash it repeatedly with distilled water and anhydrous ethanol for many times. The product is vacuum dried at 60 ° C for 48 h to obtain MoS2.
[0090] Characterization of MoS2
[0091] The basic morphology of MoS2 was observed by scanning electron microscopy (SEM). Figure 2a As shown in Figure 1, MoS2 synthesized by hydrothermal method is composed of multi-layer two-dimensional nanosheets with a particle size of about 400nm. Its crystal structure was verified by X-ray powder diffractometer (XRD) analysis. The results are shown in Figure 1. Figure 2b As shown, the XRD pattern of the obtained MoS2 corresponds to the standard card (PDF#04-008-2233), indicating that we have successfully prepared MoS2.
[0092] S2: preparing MnFe2O4;
[0093] In the S2, the preparation steps of MnFe2O4 are as follows:
[0094] S21: In this experiment, MnCl2·4H2O, FeCl3·6H2O and NaOH were the main co-precipitates. Mn :M Fe =1:4 ratio, MnCl2·4H2O and FeCl3·6H2O are accurately dissolved in a certain amount of distilled water to obtain a salt solution;
[0095] S22: Under magnetic stirring, NaOH solution was added to the salt solution, the pH value was maintained at 9, and the mixture was vigorously stirred at room temperature for 30 min to obtain a brown-black colloidal mixture;
[0096] S23: Then, the brown-black colloidal mixture is placed into a polytetrafluoroethylene liner, and the liner is placed into a high-pressure reactor, and a constant temperature reaction is carried out at 200° C. for 16 hours;
[0097] S24: Wash with distilled water and anhydrous ethanol for multiple times, dry the product in vacuum at 60°C for 48h, and grind to obtain MnFe2O4.
[0098] Structural Characterization of MnFe2O4
[0099] SEM images of MnFe2O4 nanomaterials Figure 3a As shown in Figure 2, the morphology of MnFe2O4 is irregular nanocube-like, such as Figure 3b As shown, by analyzing the XRD spectrum, it is shown that we have successfully synthesized MnFe2O4 nanomaterials.
[0100] S3: Preparation of MoS2@MnFe2O4 nanocomposite materials;
[0101] In S3, the preparation steps of the MoS2@MnFe2O4 nanocomposite material are as follows:
[0102] S31: First, weigh 0.462 g of MnFe2O4 and put it into 10 ml of deionized water, and ultrasonically vibrate for 30 minutes to obtain solution A;
[0103] S32: Dissolve 1.235 g of ammonium molybdate and 1.052 g of thioacetamide in 10 mL of deionized water and stir evenly to obtain solution B;
[0104] S33: Solution A and solution B were mixed and placed in a shaker for 30 min, and then transferred to a high-pressure reactor for reaction at 220° C. for 8 h;
[0105] S34: Wash with distilled water and anhydrous ethanol for several times, and dry the product in vacuum at 60°C for 48h.
[0106] Structural characterization of MoS2@MnFe2O4 with different synthesis ratios
[0107] During the synthesis of MoS2@MnFe2O4, we also explored the effect of different molar ratios of MnFe2O4 and MoS2 on the structure of the composite material. Figure 4a As shown in Figure 2, the SEM analysis results show that the morphology of the composite material still maintains the nanoflower shape under different molar ratios of MoS2 and MnFe2O4. Figure 4b The DLS analysis results showed that the size of the composite materials with different molar ratios did not differ significantly, and all remained around 500 nm, which was consistent with the SEM results. Figure 4c ,The XRD spectrum shows that with the increase of the proportion of MnFe2O4, the intensity of some characteristic peaks of MnFe2O4 is significantly enhanced.
[0108] Performance characterization of MoS2@MnFe2O4 with different synthesis ratios
[0109] The magnetocaloric and piezoelectric properties of MoS2@MnFe2O4 synthesized at different molar ratios are very different. Figure 5a As shown in Figure 2, the magnetocaloric heating curve in an alternating magnetic field (AMF) shows that the magnetocaloric properties of the MoS2@MnFe2O4 nanocomposite are proportional to the proportion of MnFe2O4. Figure 5b As shown in Figure 2, the ability of MoS2@MnFe2O4 to generate ROS by ultrasound is inversely proportional to the proportion of MnFe2O4. Figure 5c It shows that the performance of ROS generated by ultrasonic irradiation of MoS2@MnFe2O4 at 45°C is improved compared with that at room temperature. Through the analysis of its performance, we finally selected the composite condition with a molar ratio of MnFe2O4:MoS2=2:1.
[0110] S4: Preparation of MoS2@MnFe2O4@PVP (MMP for short);
[0111] In the S4, the preparation steps of MoS2@MnFe2O4@PVP are as follows:
[0112] S41: 10 mg of MoS2@MnFe2O4 nanoparticles were dissolved in 10 mL of deionized water and ultrasonically shaken for 30 min to obtain a black suspension A;
[0113] S42: Dissolve 40 mg of polyvinyl pyrrolidone in 10 mL of deionized water to obtain a clear and transparent solution B;
[0114] S43: Under the action of ultrasound, solution A was slowly added dropwise to solution B, and ultrasound was continued for 10 min. Then, the solution was placed in a 37°C constant temperature shaker and shaken at 180 rpm for 12 h to obtain solution C.
[0115] S44: Solution C was repeatedly washed with anhydrous ethanol and deionized water for three times, dried under vacuum at 60°C overnight and ground to obtain MoS2@MnFe2O4@PVP nanoparticles.
[0116] Structural characterization of MMPs
[0117] The surface morphology and microstructure of the material were observed using SEM. Figure 6a As shown in Figure 1, the MMP synthesized by hydrothermal method has a nanoflower-like structure with a rough surface and an average particle size of 490 nm. The basic morphology of the material was observed using a transmission electron microscope (TEM). Figure 6b As shown in Figure 2, the TME image clearly shows that MoS2 nanosheets grow in situ on the surface of MnFe2O4, and multilayer nanosheets wrap the nanocubes to form a core-shell structure with abundant wrinkles on the surface. Figure 6c As shown in the figure, Mn, Fe, and O elements are mainly distributed in the nucleus, while Mo and S elements are mainly distributed in the shell. The results further show that the two-dimensional MoS2 nanosheets are evenly distributed on the surface of MnFe2O4. Figure 6d As shown in the XRD spectrum analysis, compared with the standard cards of MnFe2O4 (PDF#04-004-5458) and MoS2 (PDF#04-008-2233), the results show that the diffraction peaks match, and the characteristic peaks of MnFe2O4 and MoS2 exist in MMP, proving that the nanoparticles are successfully composited. Figure 6e As shown, the peak is located at 1279 cm -1 The 1660 cm -1 The strong peak at indicates the presence of C=O stretching vibration absorption from the pyrrolidone ring.
[0118] Magnetocaloric and piezoelectric properties of MMP
[0119] like Figure 7a As shown, UV-Vis diffuse reflectance spectra (UV-Vis-DRS) of the different samples were obtained to measure the changes in their optical properties. The larger absorbance of MMP compared to MnFe2O4 indicates a higher tendency for activation by exogenous stimuli with lower energy in MMP. In addition, photoluminescence spectroscopy (PL) was used to measure the electron-hole combination efficiency of various samples. Figure 7bAs shown in Figure 2, MMP exhibits lower photoluminescence intensity compared to MoS2, which may be due to the formation of heterojunction that accelerates charge separation. In addition, EIS tests were performed to evaluate the charge transfer efficiency, such as Figure 7c As shown in the figure, compared with MnFe2O4 and MoS2, MMP exhibits the smallest electrical impedance, indicating that the composite of MnFe2O4 and MoS2 reduces the electron transfer resistance, and the interface of MMP can promote charge transfer, thanks to the successful construction of the heterojunction. Figure 7d As shown in Figure 2, under 5 cycles of ultrasound irradiation, MMP showed good current responsiveness. Secondly, we further explored the types of ROS produced by MMP nanomaterials and the ROS production capacity under different stimulation conditions by electron spin resonance spectroscopy (ESR), such as Figure 7e As shown, MMP can generate singlet oxygen ( 1 O2); and the MMP+US+45℃ group had a more distinct 1:1:1 1 O2 characteristic peak, this is due to the reduction of the band gap through the composite of MnFe2O4 and MoS2, thereby enhancing its ultrasonic catalytic effect; at the same time, higher temperature accelerates the electron transfer rate by increasing the entropy of the chemical reaction, and promotes the effective separation of electrons and holes; and the ROS intensity generated by the composite material is stronger than that of the single material, which further verifies the successful construction of the heterojunction and the improvement of the sonodynamic performance.
[0120] In order to clarify the generation mechanism of the above ROS, the band gap and valence band of MnFe2O4 and MoS2 were tested respectively. First, the band gap values (E g ) are 1.27eV and 1.56eV respectively; the valence band values (E VB ) are 1.05V and 0.79V respectively. According to formula E CB =E VB -E g The conduction band positions of MnFe2O4 and MoS2 are -0.22V and -0.77V respectively. Therefore, the energy band structure diagram of MMP is drawn ( Figure 7f ) It can be seen that MnFe2O4 and MoS2 can form a Z-type heterojunction.
[0121] In order to explore the magnetic effect of MMP, Figure 7gAs shown in the figure, we detected the hysteresis loop of MMP by vibrating sample magnetometer. At room temperature, the coercivity of MMP was 62.123Oe and the saturation magnetization intensity reached 11.42068emu / g. This result shows that MMP has ferromagnetism and can generate heat through hysteresis loss mechanism under the action of AMF. We tested the magnetothermal heating effect of different concentrations of MMP in AMF, such as Figure 7h As shown in the figure, the magnetothermal effect of MMP is positively correlated with its concentration; 0.5 mg / mL of MMP can be heated to 47°C in AMF within 10 minutes, and this temperature can inhibit bacterial growth. Figure 7i As shown, the magnetocaloric temperature rise curve hardly changed during the 5 cycles of applying AMF, indicating that MMP has good magnetocaloric stability. MMP has good magnetocaloric ability in vitro and can be used in antibacterial applications.
[0122] Characterization of MMP dual enzyme activity
[0123] Due to the presence of multiple variable-valent metals, MMPs are likely to have nanozyme activity. Therefore, TMB was selected as a substrate to verify whether it is POD-like. Subsequently, the POD-like enzyme activity of MMPs under different treatment conditions was evaluated. H2O2 was added to the colorimetric reaction mixture to produce ·OH under the catalysis of H2O2 by POD-like nanozymes, which can oxidize colorless TMB into blue oxidized TMB (oxTMB). Figure 8a As shown in the figure, MMP+TMB+H2O2 has an obvious absorption peak at 652nm, which indicates that MMP has good POD enzyme activity. MMP+TMB has no absorption peak at 652nm, thus excluding oxidase activity. Figure 8b As shown in the figure, under the same concentration of H2O2 and TMB, the absorption value of MMP+AMF+US at 652nm is the highest. Subsequently, 5,5-dimethyl-1-pyrroline N-oxide (DMPO) was used as a spin probe to detect the content of ·OH by ESR. Figure 8c As shown, MMP+AMF+US showed the best efficiency, which further clarified that magnetothermal synergistic piezoelectricity plays an important role in enhancing POD-like. Proportional to the substrate concentration, in contrast, the POD-like activity of MMP+AMF+US was better than that of other groups. Since MMP can catalyze H2O2 to produce O2, the enzyme-like activity of MMP was evaluated by measuring the content of O2 produced using a dissolved oxygen meter. Figure 8dAs shown in the figure, when in a slightly acidic medium (pH = 5.4, 6.5), MMP exhibits poor CAT-like activity. When in a neutral medium (pH = 7.4), the O2 production of MMP is very significant, which indicates that MMP has good CAT-like activity and can produce oxygen in the bacterial infection microenvironment. In addition, the yellow precipitate of titanium peroxide complex generated by the reaction of H2O2 and titanium sulfate is dissolved in strong acid, and its yellow color is inversely proportional to the concentration of hydrogen peroxide. The absorbance at 410nm is detected by a spectrophotometer. Figure 8e It can be seen that the absorbance of MPP+AFM+US is the lowest at 412nm, indicating that the CAT-like activity of MMP is best under the stimulation of magnetic heat and ultrasound.
[0124] S5: Determine the antibacterial properties of MoS2@MnFe2O4@PVP nanocomposites;
[0125] In S5, acquired pneumonia infection is usually caused by two common multidrug-resistant bacteria, methicillin-resistant Staphylococcus aureus (MRSA) and multidrug-resistant Klebsiella pneumoniae (MDR-Kp). The antibacterial properties of the nanocomposite materials were studied by using MRSA and MDR-Kp as model bacteria, and the plate coating method was used to study the in vitro antibacterial effect of the nanocomposite materials. The plate coating method can intuitively demonstrate the inactivation ability of MMP on MRSA and MDR-Kp. Figure 9a As shown, there was no significant reduction in the colonies after co-incubation with saline and applying stimulation conditions to them;
[0126] like Figure 9b As shown in the figure, under the synergistic effect of magnetic heat and ultrasound, the antibacterial efficiency of the nanocomposite material against MRSA and MDR-Kp reached 99.5% and 99.8% respectively, and the nanocomposite material had in vitro antibacterial ability. This is because the mechanical force of ultrasound alone and the short-lived ROS cannot completely destroy the thick cell wall structure of bacteria, and the limited temperature can only inhibit their growth, and cannot have a significant bactericidal effect. In contrast, the bactericidal effect is particularly obvious under the synergistic effect of magnetic heat and ultrasound.
[0127] S6: Evaluation of the anti-biofilm ability of MoS2@MnFe2O4@PVP nanocomposites in vitro;
[0128] In S6, MRSA and MDR-Kp were used to evaluate the in vitro anti-biofilm activity, and the evaluation steps were as follows:
[0129] S61: Place a 9 mm cell slide into a 24-well plate and add 1 mL of 1×10 7 CFU / mL of MRSA or MDR-Kp suspension was inoculated into the wells containing cell slides;
[0130] S62: Incubate continuously in a biochemical incubator at 37°C for 96 hours, during which the culture medium is replaced every 24 hours to form a biofilm on the surface; after the biofilm is formed, wash repeatedly with sterile saline to remove unbound bacteria;
[0131] S63: Fig.10a As shown, after treatment under different conditions, the bacteria were labeled with SYTO9 and PI dyes in a dark environment, incubated for 30 minutes, and rinsed three times with sterile saline. The fluorescence imaging effect of live and dead bacteria was obtained under a laser confocal microscope.
[0132] S64: In MDR-Kp or MRSA, the mortality of each group treated with MMP was higher than that of the control group, proving that the nanocomposite played a significant role in destroying the biofilm. At the same time, in the final group, MMP showed a better biofilm destruction effect under the synergistic stimulation of magnetic heat and ultrasound, and the antibacterial potential of MMP was maximized and utilized.
[0133] S7: Verify the therapeutic effect of MoS2@MnFe2O4@PVP nanocomposite on bacterial pneumonia in vivo.
[0134] In S7, the steps of verifying the treatment effect are as follows:
[0135] S71: To further verify the potential of MMP in treating bacterial pneumonia, a BALB / C mouse lung infection model induced by MDR-Kp was established, and seven different groups were treated, including PBS, PBS+AMF+US, MMP, MMP+US, MMP+AMF, MMP+AMF+US, and Health;
[0136] S72: Lung tissue homogenate was collected and smeared on the 3rd day after treatment, and the residual bacteria in the lung tissue were evaluated by plate smear counting method;
[0137] S73: Fig.11a -b shows that there were obvious bacteria in the lung tissues of other treatment groups, and the bacteria in the lungs of mice treated with MMP+AMF+US were significantly reduced; the expression of co-stimulatory molecules CD206 / CD86 was analyzed by immunohistochemical staining (IHC) of dissected lung tissues.
[0138] S74: The results are as follows Fig.11cAs shown, in the PBS group, PBS+AMF+US group, and MMP group, CD86 was highly expressed in the lungs, which enhanced the inflammatory response and induced lung damage; in the MMP+AMF+US group, CD86 protein was significantly downregulated, while CD206 expression was at its peak. MMP+AMF+US treatment has antibacterial ability in mice, and helps polarize M1 macrophages to M2 phenotype, inhibiting the development of inflammation.
[0139] The above is only a preferred embodiment of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made without departing from the principles of the present invention, and these improvements and modifications should also be considered as the protection scope of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention shall be implemented according to the conventional means in the art unless otherwise specified and limited.
Claims
1. A method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers, characterized in that: The preparation method comprises the following steps: S1: Preparation of MoS2; S2: preparing MnFe2O4; S3: Preparation of MoS2@MnFe2O4 nanocomposite materials; S4: Preparation of MoS2@MnFe2O4@PVP; S5: Determine the antibacterial properties of MoS2@MnFe2O4@PVP nanocomposites; S6: Evaluation of the anti-biofilm ability of MoS2@MnFe2O4@PVP nanocomposites in vitro; S7: Verify the therapeutic effect of MoS2@MnFe2O4@PVP nanocomposite on bacterial pneumonia in vivo.
2. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In the S1, the preparation steps of MoS2 are as follows: Weigh 1.235 g of ammonium molybdate and 1.052 g of thioacetamide and dissolve them in 20 mL of deionized water. Stir evenly to obtain a colorless transparent solution. Transfer it to a 50 mL high-pressure reactor and react at 220 ° C for 8 h. Wash it repeatedly with distilled water and anhydrous ethanol for many times. The product is vacuum dried at 60 ° C for 48 h to obtain MoS2.
3. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In the S2, the preparation steps of MnFe2O4 are as follows: S21: MnCl2·4H2O, FeCl3·6H2O and NaOH are the main co-precipitates, and M Mn :M Fe =1:4 ratio, MnCl2·4H2O and FeCl3·6H2O are accurately dissolved in a certain amount of distilled water to obtain a salt solution; S22: Under magnetic stirring, NaOH solution was added to the salt solution, the pH value was maintained at 9, and the mixture was vigorously stirred at room temperature for 30 min to obtain a brown-black colloidal mixture; S23: Then, the brown-black colloidal mixture is placed into a polytetrafluoroethylene liner, and the liner is placed into a high-pressure reactor, and a constant temperature reaction is carried out at 200° C. for 16 hours; S24: Wash with distilled water and anhydrous ethanol for multiple times, dry the product in vacuum at 60°C for 48h, and grind to obtain MnFe2O4.
4. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In S3, the preparation steps of the MoS2@MnFe2O4 nanocomposite material are as follows: S31: First, weigh 0.462 g of MnFe2O4 and put it into 10 ml of deionized water, and ultrasonically vibrate for 30 minutes to obtain solution A; S32: Dissolve 1.235 g of ammonium molybdate and 1.052 g of thioacetamide in 10 mL of deionized water and stir evenly to obtain solution B; S33: Solution A and solution B were mixed and placed in a shaker for 30 min, and then transferred to a high-pressure reactor for reaction at 220° C. for 8 h; S34: Wash with distilled water and anhydrous ethanol for several times, and dry the product in vacuum at 60°C for 48h.
5. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In the S4, the preparation steps of MoS2@MnFe2O4@PVP are as follows: S41: 10 mg of MoS2@MnFe2O4 nanoparticles were dissolved in 10 mL of deionized water and ultrasonically shaken for 30 min to obtain a black suspension A; S42: Dissolve 40 mg of polyvinyl pyrrolidone in 10 mL of deionized water to obtain a clear and transparent solution B; S43: Under the action of ultrasound, solution A was slowly added dropwise to solution B, and ultrasound was continued for 10 min. Then, the solution was placed in a 37°C constant temperature shaker and shaken at 180 rpm for 12 h to obtain solution C. S44: Solution C was repeatedly washed with anhydrous ethanol and deionized water for three times, dried under vacuum at 60°C overnight and ground to obtain MoS2@MnFe2O4@PVP nanoparticles.
6. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In said S5, the antibacterial properties of the nanocomposite materials were studied using MRSA and MDR-Kp as model bacteria by using a plate coating method, and the colonies did not significantly decrease after co-incubation with physiological saline and applying stimulation conditions thereto; Under the synergistic effect of magnetic heat and ultrasound, the antibacterial efficiency of the nanocomposite material against MRSA and MDR-Kp reached 99.5% and 99.8% respectively, and the nanocomposite material had in vitro antibacterial ability.
7. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 6, characterized in that: In S6, MRSA and MDR-Kp were used to evaluate the in vitro anti-biofilm activity, and the evaluation steps were as follows: S61: Place a 9 mm cell slide into a 24-well plate and add 1 mL of 1×10 7 CFU / mL of MRSA or MDR-Kp suspension was inoculated into the wells containing cell slides; S62: Incubate continuously in a biochemical incubator at 37°C for 96 hours, during which the culture medium is replaced every 24 hours to form a biofilm on the surface; after the biofilm is formed, wash repeatedly with sterile saline to remove unbound bacteria; S63: After treatment under different conditions, the bacteria were labeled with SYTO9 and PI dyes in dark conditions, incubated for 30 min, rinsed three times with sterile saline, and the fluorescence imaging effect of live and dead bacteria was performed under a laser confocal microscope; S64: In MDR-Kp or MRSA, the mortality of the MMP-treated groups was higher than that of the control group, demonstrating that the nanocomposite played a significant role in disrupting the biofilm.
8. The method for preparing magnetocaloric nanoparticles based on piezoelectric catalytic molybdenum disulfide nanoflowers according to claim 1, characterized in that: In S7, the steps of verifying the treatment effect are as follows: S71: A BALB / C mouse lung infection model induced by MDR-Kp was established, and 7 different groups were treated separately, including PBS, PBS+AMF+US, MMP, MMP+US, MMP+AMF, MMP+AMF+US, and Health; S72: Lung tissue homogenate was collected and smeared on the 3rd day after treatment, and the residual bacteria in the lung tissue were evaluated by plate smear counting method; S73: There were obvious bacteria in the lung tissues of other treatment groups, and the number of bacteria in the lungs of mice treated with MMP+AMF+US was significantly reduced; S74: In the PBS group, PBS+AMF+US group, and MMP group, CD86 was highly expressed in the lungs, which enhanced the inflammatory response and induced lung injury; in the MMP+AMF+US group, CD86 protein was significantly downregulated, while CD206 expression was at its peak, and MMP+AMF+US treatment had antibacterial ability in mice.
Citation Information
Patent Citations
Platinum nanoparticle doped molybdenum disulfide nanosheet as well as preparation method and application thereof
CN117883568A
Preparation method and application of inhalable sound-magnetic-gas integrated nano preparation for efficiently treating bacterial pneumonia
CN118766873A
Cited By
An acoustomagnetic coupling piezoelectric nanosen and a preparation method and application thereof in antibiosis
CN122721598A